Treatment of Enteropathogenic Escherichia coli Diarrhea in Cancer Patients: A Series of Three Cases - James D. Denham; Sowmya Nanjappa; John N. Greene (Case Reports in Infectious Diseases)
Enteropathogenic Escherichia coli (EPEC) is a common cause of watery diarrhea in children in the developing world and an infrequent cause of significant diarrhea in adult patients. EPEC diarrhea, while not commonly seen in cancer patients, can cause significant distress to patients, and antimicrobial choice for this condition in this patient population is not clearly delineated in the literature. We report 3 cases of EPEC diarrhea in cancer patients and discuss the use of azithromycin for successful treatment of these patients. Positive outcomes were seen while using azithromycin in our first two patients and ciprofloxacin in our third patient.